Viral intestinal infections in young children in Baku - F. V. Qilindjova (LLC "Diagnostics and Vaccines", 2023)
Viral pathogens are a common cause of acute intestinal infections, especially in young children. The purpose of the work is to assess the role of acute intestinal infection of viral etiology in children in Baku, depending on age. Materials and methods. 117 patients under the age of 3 years who were admitted to the Children's City Clinical Hospitals No. 1 and No. 7 of Baku with a diagnosis of «Acute intestinal infection» in 2019 were under observation. Etiological diagnosis of viral gastroenteritis of various etiologies (rotavirus, adenovirus and astrovirus) was carried out using enzyme immunoassay and immunochromatography. Results. Of the 117 samples examined, 58.9% of cases detected viral pathogens, namely group A rotavirus (RV) - 27.4 ± 4.1%, adenovirus 40/41 serotypes (AdV) - 18.8 ± 3.6%, and human astrovirus (HAstV) - 12.8 ± 3.1%. With rotavirus infection, the frequency of detection of pathogens increased from 26.7 ± 11.4% in children of the first year of life to 33.8 ± 5.4% in children in the age group of 1-3 years. The largest number of mono-adenoviral intestinal infections (40/41 serotypes) was detected in children aged 7-12 months - 33.3 ± 12.2%. It was found that human astroviruses were also detected most often in children aged 7- 12 months - 20.0 ± 10.3%. It was found that among mixed viral intestinal infections in young children, the association RV + AstV was more common (6.8 ± 2.3%). Among mixed cultures, the association frequency of RV + C. albicans prevailed and amounted to 7.7 ± 2.5% with predominant detection in the age group of 7- 12 months. - 20.0 ± 10.3%.